The costs of electoral fraud: establishing the link between electoral integrity, winning an election, and satisfaction with democracy. Issue 3 (3rd July 2017) - Fortin-Rittberger, Jessica; Harfst, Philipp; Dingler, Sarah C.
ABSTRACT: Previous research has shown that voters' perception of electoral fairness has an impact on their attitudes and behaviors. However, less research has attempted to link objective measurements of electoral integrity on voters' attitudes about the democratic process. Drawing on data from the Comparative Study of Electoral Systems and the Quality of Elections Data, we investigate whether cross-national differences in electoral integrity have significant influences on citizens' level of satisfaction with democracy. We hypothesize that higher levels of observed electoral fraud will have a negative impact on evaluations of the democratic process, and that this effect will be mediated by a respondent's status as a winner or loser of an election. The article's main finding is that high levels of electoral fraud are indeed linked to less satisfaction with democracy. However, we show that winning only matters in elections that are conducted in an impartial way. The moment elections start to display the telltale signs of manipulation and malpractice, winning and losing no longer have different effects on voter's levels of satisfaction with democracy.